THE HISTORY OF 27 SQUADRON SAAF - Meyer, A.C. (Scientia Militaria - South African Journal of Military Studies, 2012)
With the outbreak of the Second World War in September 1939 the vital importance of the Cape Sea Route was not immediately realized and for the first couple of years, most of the war effort was directed towards operations in East and North Africa.